Decomposing the Gender Wage Gap in the Urban Labor Market in Kenya - Alwago, Wycliffe Obwori (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
Legislation and regulation have been effective in reducing the gender wage gap in developed countries; however, the gap still exists globally, and progress towards narrowing the gap has been unacceptably slow even in regions where it is improving. This study presents the analysis of gender wage gap in Kenya’s urban labor market by using the World Bank Skills Towards Employability and Productivity Survey (WBSTEPS). This study employed Mincer earnings regressions with Heckman selection correction and the Blinder-Oaxaca and Neumark decomposition procedures to answer the research questions. The results of the wage determination and participation in the labor market show that there is no selectivity-bias problem. Personal characteristics such as education and age, as well as work-related characteristics, are important factors in determining earnings. The magnitude of the gender wage gap varies across the wage distribution, and the results of the wage decomposition reveal that women in urban Kenya earn 84.5-to-86% of men’s earnings. The earnings gap is overwhelmingly due to differences in returns to endowments, which account for between 70% and 94.7% of the total earnings gap. Admittedly, the study found evidence of discrimination against women in the returns to endowments, but also observed pronounced favoritism towards men. However, discrimination against women is more pronounced than favoritism towards men. Addressing the gender wage gap in Kenya requires a multifaceted approach that tackles both systemic biases against women and structural barriers that hinder women from accessing equal opportunities in education, training, and career advancement and government policies that minimize favoritism towards men.